2016
DOI: 10.18632/oncotarget.9305
|View full text |Cite
|
Sign up to set email alerts
|

mTOR: An attractive therapeutic target for osteosarcoma?

Abstract: Osteosarcoma (OS) is a common primary malignant bone tumor with high morbidity and mortality in children and young adults. How to improve poor prognosis of OS due to resistance to chemotherapy remains a challenge. Recently, growing findings show activation of mammalian target of rapamycin (mTOR), is associated with OS cell growth, proliferation, metastasis. Targeting mTOR may be a promising therapeutic approach for treating OS. This review summarizes the roles of mTOR pathway in OS and present research status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 80 publications
1
42
0
1
Order By: Relevance
“…Recent research has reported the aberrant activation of mTOR in OS . Focal adhesion kinase is reported to regulate the activity of the AKT pathway, suggesting a possible mechanistic link in OS .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has reported the aberrant activation of mTOR in OS . Focal adhesion kinase is reported to regulate the activity of the AKT pathway, suggesting a possible mechanistic link in OS .…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has reported the aberrant activation of mTOR in OS. (18) Focal adhesion kinase is reported to regulate the activity of the AKT pathway, suggesting a possible mechanistic link in OS. (19) Therefore, we chose 143B and MG63 cell lines, which were most sensitive to PF562271 treatment, to examine the expression of the AKT/mTOR pathway after PF562271 treatment for 24 h. PF562271 downregulated FAK (Y397), AKT (S473), and mTOR (S2448) phosphorylation at concentrations that impaired cell growth and colony formation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aberrant expression of mTor has been shown to be essential for the tumorigenesis of the majority of all cancers [811], including OS [12]. Recently, the membrane-associated E3 ubiquitin ligase ZNRF2 has been shown to be involved in the activation and regulation of mTor through protein interaction [13].…”
Section: Introductionmentioning
confidence: 99%